The Pathogenesis of Neurotrauma Indicates Targets for Neuroprotective Therapies - Kwiecien, Jacek M. (Current Neuropharmacology, 2021)
The spinal cord injury (SCI) initiates an extraordinarily protracted disease with 3 phases; acute, inflammatory, and resolution that are restricted to the cavity of injury (COI) or arachnoiditis by a unique CNS reaction against the severity of destructive inflammation. While the severity of inflammation involving the white matter is fueled by a potently immunogenic activity of damaged myelin, its sequestration in the COI and its continuity with the cerebrospinal fluid of the subdural space allow anti-inflammatory therapeutics infused subdurally to inhibit phagocytic macrophage infiltration and thus provide neuroprotection. The role of astrogliosis in containing and ultimately in eliminating severe destructive inflammation post-trauma appears obvious but is not yet sufficiently understood to use in therapeutic neuroprotective and neuroregenerative strategies. An apparent antiinflammatory activity of reactive astrocytes is paralleled by their active role in removing excess edema fluid in blood-brain barrier damaged by inflammation. Recently elucidated pathogenesis of neurotrauma, including SCI, traumatic brain injury (TBI), and stroke, calls for the following principal therapeutic steps in its treatment leading to the recovery of neurologic function: (1) inhibition and elimination of destructive inflammation from the COI with accompanying reduction of vasogenic edema, (2) insertion into the COI of a functional bridge supporting the crossing of regenerating axons, (3) enabling regeneration of axons to their original synaptic targets by temporary safe removal of myelin in targeted areas of white matter, (4) in vivo, systematic monitoring of the consecutive therapeutic steps. The focus of this paper is on therapeutic step 1.
Keywords: astrogliosis